Striving to Make Massage Therapy Accessible to Older Adults: an Interview with Niki Munk, PhD, LMT - Kennedy, LMT, BCTMB, DrPH, Executive Editor, IJTMB, Ann Blair (International Journal of Therapeutic Massage & Bodywork, 2018)
First she became a licensed massage therapist in Kentucky. Then, in a quest to improve the care she provided to her elderly clinical population, Niki Munk continued her journey by furthering her education and receiving her doctorate in ger-ontology. Dr. Munk, a massage therapy researcher at Indiana University’s IUPUI campus, shares in this interview her optimism on the future of the massage therapy profession and massage therapy research. Dr. Munk also provides insight into the way she makes decisions, and from whom she would like to receive advice.